Knowledge, attitude and practice toward childhood immunization among mothers in Lebanon - Sara Saleh; Pia Chedid (PLoS ONE, 2025)
Background Barriers to childhood immunization in Lebanon are multifaceted. While Lebanon has historically maintained high immunization coverage, recent socio-economic challenges and recurrent political crisis have strained the healthcare system, leading to decreased vaccination rates. The knowledge, attitudes, and practices (KAP) of mothers play a key role in determining whether their children receive recommended immunizations. The aim of this study was to assess the KAP of Lebanese mothers regarding childhood immunization and to identify potential barriers to vaccination in children. Methods A cross-sectional study was conducted among Lebanese mothers with children aged between zero days to 5 years old. A stratified random sampling method was used and a structured questionnaire was administered to collect data on KAP regarding childhood immunization. Descriptive statistics were performed. Chi-square test and linear regression were used to assess the association between KAP and sociodemographic factors with significance set at p < 0.05. Results Most mothers demonstrated good knowledge (86.3%) and positive attitudes (94.8%) toward vaccination. However, only 43.3% exhibited good vaccination practices. Significant disparities were observed in rural regions such as Beqaa, where mothers had the lowest education levels, the highest rates of poor knowledge (11.9%), and the lowest vaccination practice scores (32.7%). Employment was significantly associated with higher knowledge scores (p = 0.002, 95% CI: -1.42 to -0.33), while household income was significantly associated with attitudes (p = 0.009, 95% CI: -0.96 to -0.13) and vaccination practices (p = 0.002, 95% CI: -0.48 to -0.11). Vaccine unavailability and cost were frequently cited as barriers, particularly in rural regions. Conclusions Discrepancy between knowledge and attitude v/s practice suggests that a number of barriers prevent mothers from translating their good knowledge and positive attitude into action. Significant regional disparities exist, with rural areas like Beqaa facing the greatest challenges. Strengthening vaccine accessibility, implementing targeted educational interventions, and increasing governmental support are critical to improving immunization coverage nationwide.